2008
DOI: 10.1007/s00268-008-9579-8
|View full text |Cite
|
Sign up to set email alerts
|

Is Total Thyroidectomy the Surgical Procedure of Choice for Benign Multinodular Goiter? An Evidence‐Based Review

Abstract: Total thyroidectomy is the procedure of choice for the surgical management of benign multinodular goiter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
156
1
12

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(185 citation statements)
references
References 61 publications
16
156
1
12
Order By: Relevance
“…It is reported that differentiated thyroid cancer may be detected in up to 10% of patients undergoing surgical procedures for benign thyroid disease, in post-operative histopathological evaluation (8,9). In the literature, completion thyroidectomy is recommended for such cases (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that differentiated thyroid cancer may be detected in up to 10% of patients undergoing surgical procedures for benign thyroid disease, in post-operative histopathological evaluation (8,9). In the literature, completion thyroidectomy is recommended for such cases (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Several assumptions led to this widely shared behavior. The major reasons included the following: low complication rate associated with TT (as reported by several authors) [27][28][29], risk of relapse after hemithyroidectomy [5,7], risk of an occult malignancy [30] that makes follow-up complex, and/or greater difficulty in performing the revision surgery after thyroid lobectomy. Several recent studies have emphasized various advantages of hemithyroidectomy [31,32] in selected cases of malignancy [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…TT was used as a surgical treatment for a wide range of thyroid diseases including solitary benign nodules [6,26,27]. Several assumptions led to this widely shared behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Given these disadvantages, it is controversial whether there is a benefit in terms of postoperative complications compared to total thyroidectomy [22,23].…”
Section: Surgical Treatmentmentioning
confidence: 99%